Structure, positions and mechanisms: A case study of two Dutch Salafi-Jihadi networks - van Nassau, Casper S. (European journal of criminology, 2024)
Social network analysis can be a powerful tool to better understand the social context of terrorist activities, and it may also offer potential leads for agencies to intervene. Our access to Dutch police information allows us to analyse the relational features of two networks that include actors who planned acts of terrorism and were active in the dissemination of a Salafi-Jihadi interpretation of Islam (n?=?57; n?=?26). Based on a mixed-method approach that combines qualitative and more formal statistical analysis (exponential random graph models), we analyse the structural characteristics of these networks, individual positions and the extent to which radical leaders, pre-existing family and friendship ties and radicalizing settings affect actors to form ties. We find that both networks resemble a core?periphery structure, with cores formed by a densely interconnected group of actors who frequently meet in radicalizing settings. Based on our findings, we discuss the potential effects of preventive and repressive measures developed within the Dutch counterterrorism framework.